Students’ opinions on the need for interactive multimedia development for entrepreneurship learning - Mochamad Kamil Budiarto; Triana Rejekiningsih; Sudiyanto Sudiyanto (International Journal of Evaluation and Research in Education (IJERE), 2021)
The use of information technology in education has the potential to have positive outcomes in the face of globalization. This study aimed to identify various needs in order to integrate technology into learning. The study employed a quantitative approach with a survey method to senior high schools. The questionnaire was used as a data collection instrument which was distributed to a research sample of 60 students who were randomly selected. The results revealed that students' attitudes toward the integration of technology into the learning process are inversely proportional to their use of learning media, which is still limited to the printed module. Students would like to create interactive multimedia as a medium for learning craftsmanship and entrepreneurship, based on the needs of students who are technologically literate and efforts to optimize the use of facilities that available at school.